Efficient access to alkynylated quinalizinones via the gold(I)-catalyzed aminoalkynylation of alkynes - Shinde, Popat S.; Shaikh, Aslam C.; Patil, Nitin T. (Chemical Communications, 2016)
The gold-catalyzed aminoalkynylation of alkynes for the synthesis of quinalizinones is reported. For instance, the reaction of pyridinoalkynes with 1-[(triisopropylsilyl)-ethynyl]-1,2-benziodoxol-3(1H)-one (TIPS-EBX) in the presence of a catalytic amount of AuCl at 50 8C afforded alkynylated quinalizinones in 57-87% yields.

Gold-catalyzed dehydrazinative C(sp)-S coupling reactions of arylsulfonyl hydrazides with ethynylbenziodoxolones for accessing alkynyl sulfones - Shinde, Popat S.; Patil, Nitin T. (European Journal of Organic Chemistry, 2017)
A gold(III)-catalyzed dehydrazinative coupling reaction between arylsulfonyl hydrazides and ethynylbenziodoxolone reagents was realized for the synthesis of alkynyl sulfones. The scope and versatility of the reaction were demonstrated by the efficient synthesis of 23 derivatives with diverse structural features.

Catalytic enantioselective 1,3-alkyl shift in alkyl aryl ethers: efficient synthesis of optically active 3,3 '-diaryloxindoles - Gade, Amol B.; Bagle, Pradip N.; Shinde, Popat S.; Bhardwaj, Vipin; Banerjee, Subhrashis; Chande, Ajit; Patil, Nitin T. (Angewandte Chemie-International Edition, 2018)
Reported is the first organocatalytic asymmetric 1,3-alkyl shift in alkyl aryl ethers for the synthesis of chiral 3,3'-diaryloxindoles using a chiral Bronsted acid catalyst. Preliminary results showed that each enantiomer of the 3,3'-diaryloxindole, and a racemic mixture, showed different antiproliferative activities against HeLa cell lines by using an MTT assay.

Gold(I)-catalyzed cross-coupling reactions of aryldiazonium salts with organostannanes - Akram, Manjur O.; Shinde, Popat S.; Chintawar, Chetan C.; Patil, Nitin T. (Organic & Biomolecular Chemistry, 2018)
Gold(I)-catalyzed cross-coupling reactions of aryldiazonium salts with organostannanes are described. This redox neutral strategy offers an efficient approach to diverse biaryls, vinyl arenes and arylacetylenes. Monitoring the reaction with NMR and ESI-MS provided strong evidence for the in situ formation of Ph3PAuIR (R = aryl, vinyl and alkynyl) species which is crucial for the activation of aryldiazonium salts.

Interplay of anion-pi(+) and pi(+)-pi(+) interactions in novel pyrido[2,1-a]isoquinolinium-based aiegens - substituent- and counterion-dependent fluorescence modulation and applications in live cell mitochondrial imaging - Mule, Ravindra D.; Roy, Rupam; Mandal, Koushik; Chopra, Deepak; Dutta, Tanoy; Sancheti, Shashank P.; Shinde, Popat S.; Banerjee, Somsuvra; Lal Koner, Apurba; Bhowal, Rohit; Senthilkumar, Beeran; Patil, Nitin T. (Chemistry-A European Journal, 2022)
Recently, the concept of anion-pi(+) interactions has witnessed unique applications in the field of AIEgen development. In this contribution, we disclose a consolidated study of a library of N-doped ionic AIEgens accessed through silver-mediated cyclization of pyridino-alkynes. A thorough photophysical, computational and crystallographic study has been conducted to rationalize the observed substituent- and counterion-dependent fluorescence properties of these luminogens. We further elucidate the prominent role of anion-pi(+) interactions, pi(+)-pi(+) interactions and other non-covalent interactions, in inhibiting the undesired ACQ effect. Finally, we have also demonstrated the application of selected AIEgens for imaging of mitochondria in live cells.
Keywords: 1-a]isoquinolinium; AIEgens; anion-pi(+); crystal structure; mitochondrial imaging; pyrido[2